Ceramic gel phase change energy storage self-insulation structure and preparation method thereof
By using iron tailings, silicon nitride and boron nitride to prepare porous ceramics, combined with silica and zirconium dioxide sol, the problem of insufficient durability and thermal stability of existing insulation materials is solved, and efficient phase change is achieved The energy storage and heat conduction performance are improved, forming a high-performance ceramic gel phase-change energy storage self-insulation structure.
Patent Information
- Application Number
- CN202411331864.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing insulation materials such as asbestos and glass fibers have poor durability, easy aging, flammable and environmental pollution in long-term use. Ceramic gels have limited their wide application due to their brittleness and low strength. Phase change materials have thermal stability and There is also room for improvement in energy storage efficiency.
Iron tailings, silicon nitride and boron nitride are used as raw materials to prepare porous ceramic base material, combined with silica and zirconium dioxide sol, and prepared ceramic gel phase change energy storage self-insulating structure through impregnation components and packaging coating technology. , improve thermal conductivity and mechanical strength.
The preparation of high porosity and low density porous ceramics has been achieved, which improves the energy storage efficiency and thermal physical properties of phase change materials, reduces environmental pollution, enhances the high temperature resistance and chemical stability of ceramic materials, and provides good physical and Chemical environment to ensure the stability and reliability of the phase transition process.
Smart Images

Figure BDA0005057188180000121 
Figure BDA0005057188180000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a ceramic gel phase-change energy storage self-insulation structure and a preparation method thereof. Background Art
[0002] With the growing demand for building energy conservation, improving energy efficiency and developing new insulation materials have always been hot topics in the field of energy utilization and building energy conservation. Although traditional insulation materials such as asbestos and glass fiber have certain insulation effects, they have poor durability, easy aging, flammability, environmental pollution and other problems during long-term use. Ceramic aerogel is regarded as a very promising insulation material due to its excellent thermal stability. However, the brittleness and low strength of ceramic aerogel limit its wide application. Phase change materials are widely used in the field of building energy storage because they can absorb or release a large amount of latent heat at a specific temperature.
[0003] In recent years, ceramic gel has become an ideal carrier for combining with phase change materials due to its excellent mechanical properties, chemical stability and thermal stability. Ceramic gel can not only effectively encapsulate phase change materials to prevent leakage, but also enhance thermal conductivity through its porous structure, achieving phase change energy storage while improving thermal insulation effect. Summary of the invention
[0004] Technical issues solved
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a ceramic gel phase change energy storage self-insulating structure and a preparation method thereof, aiming to prepare a self-insulating structure with better thermal insulation and energy storage effect.
[0006] Technical Solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A method for preparing a ceramic gel phase change energy storage self-insulation structure, the preparation method comprising the following steps:
[0009] Step 1, using iron tailings, silicon nitride and boron nitride as raw materials to prepare a ceramic base material, and then using the ceramic base material, deionized water, a dispersant, a gel monomer, a cross-linking agent, a foaming agent, a foam stabilizer, a catalyst and an initiator as raw materials to prepare a ceramic base green body, and obtaining a porous ceramic after sintering treatment;
[0010] Step 2, pouring ethyl orthosilicate and zirconium oxychloride into ethanol aqueous solution respectively to prepare silica sol and zirconium dioxide sol, and then mixing the silica sol and zirconium dioxide sol to prepare a composite sol;
[0011] Step 3, adding propylene oxide and paraffin to the composite sol to prepare an impregnation component, stirring at a speed of 200 r / min for 30 minutes under heating conditions, and then immersing in the preheated porous ceramic, after immersion for 10 minutes, taking out and placing at room temperature for 1-2 hours, and the obtained structure is recorded as a ceramic gel structure;
[0012] Step 4: Coat a packaging coating on the surface of the ceramic gel structure, and obtain a ceramic gel phase change energy storage self-insulating structure after drying.
[0013] Furthermore, in step 1, the preparation method of the ceramic base material is:
[0014] The iron tailings are placed in an oven at 60°C and dried for 48 hours, crushed in a crusher and then dried in an oven at 60°C for 24 hours, then crushed in a crusher again and sieved through a 200-mesh sieve, and the crushed and sieved powder is mixed with silicon nitride and boron nitride in a weight ratio of 4:2:1 to obtain a ceramic base material.
[0015] Furthermore, in step 1, the dispersant is polyvinyl alcohol, the gel monomer is acrylamide, the crosslinking agent is methylenebisacrylamide, the foaming agent is sodium dodecyl sulfate, the foam stabilizer is dodecyl alcohol, the catalyst is tetramethylethylenediamine, and the initiator is ammonium persulfate.
[0016] Furthermore, in step 1, the preparation method of the ceramic-based green body is:
[0017] S4.1, weigh 100 weight parts of deionized water, 45-48 weight parts of ceramic base material and 1-2 weight parts of dispersant, pour them into a ball mill and ball mill for 15 hours, after the ball milling is completed, add 85-90 weight parts of gel monomer and 9-10 weight parts of cross-linking agent and continue ball milling for 2 hours, the obtained result is recorded as the ball milling component;
[0018] S4.2. Add 4-5 parts by weight of foaming agent and 1-2 parts by weight of foam stabilizer to the ball-milled components, stir at a speed of 1500r / min for 10 minutes, then add 3-4 parts by weight of catalyst and 6-7 parts by weight of initiator, stir at the original speed for 30 seconds, pour into the mold, and after molding and demolding, place in an oven at 45°C and dry for 8-10 hours to obtain a ceramic-based green body.
[0019] Furthermore, in step 1, the specific operation method of the sintering process is:
[0020] The ceramic-based green body is placed in a muffle furnace, first heated to 400-500°C at a heating rate of 1.5°C / min and kept warm for 30 minutes, then heated to 800-950°C at a heating rate of 2°C / min and kept warm for 2 hours, and finally heated to 1100°C at a heating rate of 1.5°C / min and kept warm for 4 hours. The porous ceramic is obtained after the furnace is cooled.
[0021] Furthermore, in step 2, the preparation method of the composite sol is:
[0022] S6.1. Weigh a calculated amount of tetraethyl orthosilicate and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 4. The result is recorded as silica sol. The molar ratio of tetraethyl orthosilicate to ethanol in the silica sol is 1:40.
[0023] S6.2. Weigh a calculated amount of zirconium dioxide oxychloride and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 5. The result is recorded as zirconium dioxide sol. The molar ratio of zirconium dioxide oxychloride to ethanol in the zirconium dioxide sol is 1:40.
[0024] S6.3. Pour the zirconium dioxide sol into the silicon dioxide sol and stir at a speed of 200 r / min for 10 min to obtain a composite sol. The molar ratio of ethyl orthosilicate to zirconium oxychloride in the composite sol is 1:1.
[0025] Furthermore, in step 3, the weight ratio of the composite sol, propylene oxide and paraffin is 2:1:3, the heating temperature of the heating condition is 95°C, the temperature of the preheated porous ceramic is 85-90°C, and the temperature of the impregnated component during the impregnation process is 90-95°C.
[0026] Furthermore, in step 4, the specific operation of applying the encapsulation coating is:
[0027] S8.1, weigh 8-12 parts of carbon fiber, 5-8 parts of steel fiber, 3-4 parts of silane coupling agent KH-570 and 100 parts of deionized water, mix them, stir them at 48°C and 300 r / min for 10 min, and freeze-dry them to obtain the reinforcing fiber component;
[0028] S8.2. Weigh 5-8 parts of reinforcing fiber components and 45-50 parts of polyvinyl chloride by weight for melt blending, and then coat the melt blended components on the surface of the ceramic gel structure.
[0029] Furthermore, in step 4, the specific operation of the drying treatment is to place it at room temperature for 2-3 hours.
[0030] A ceramic gel phase change energy storage self-insulation structure is prepared by a method for preparing a ceramic gel phase change energy storage self-insulation structure.
[0031] Beneficial Effects
[0032] The present invention provides a ceramic gel phase change energy storage self-insulation structure and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The porous ceramics prepared by the present invention using iron tailings, silicon nitride and boron nitride as raw materials can have the properties of high porosity, low density and high specific surface area. The porous structure is conducive to the filling and distribution of phase change materials, improves energy storage efficiency, and helps to improve the heat transfer efficiency of phase change materials under high porosity conditions. Iron tailings are industrial wastes, and their recycling can reduce the pressure on the exploitation of primary resources, realize the recycling of resources, and help reduce environmental pollution and ecological damage. Silicon nitride and boron nitride are high-performance ceramic materials with excellent thermal conductivity, thermal stability and chemical stability. The porous ceramics prepared by using them as raw materials can maintain high thermophysical properties when carrying phase change materials, ensuring the stability and reliability of the phase change process. Secondly, the porous material prepared by the present invention as a carrier of phase change materials can provide a good physical and chemical environment to ensure that the phase change materials are kept in a cyclic use process. Maintaining stable performance is helpful to improve the overall efficiency and reliability of the energy storage system; the present invention prepares porous ceramics through the synergistic cooperation between iron tailings, silicon nitride and boron nitride, which can give full play to their respective advantages and improve the comprehensive properties of porous ceramics such as mechanical strength, thermal stability, corrosion resistance and wear resistance. During the sintering process, oxides such as silicon dioxide in the iron tailings can react chemically with silicon nitride and boron nitride to form stable compound phases. The formation of these compound phases helps to reduce the sintering temperature, improve the sintering efficiency, and promote the formation of porous structures, and can also enhance the high temperature resistance and chemical stability of ceramic materials; on the basis of reducing costs through iron tailings, the present invention can also combine the high thermal conductivity and high thermal stability of silicon nitride and boron nitride to improve energy storage efficiency. Compared with a single component, the porous ceramics prepared by the combination of iron tailings, silicon nitride and boron nitride in the present invention have better application prospects.
[0034] 2. The present invention mixes silica sol and zirconium dioxide sol and then adds paraffin to prepare a phase change material, which has the function of enhancing thermal conductivity and improving energy storage. Both silica and zirconium dioxide have good thermal conductivity. Mixing them with paraffin can significantly improve the thermal conduction efficiency of paraffin as a phase change material, so that heat can be transferred and distributed faster in the energy storage structure. Using a porous structure with high porosity as a carrier to carry the phase change material can help to evenly distribute heat, thereby further enhancing the thermal conductivity of the energy storage structure; secondly, the present invention disperses carbon fiber and steel fiber in polyvinyl chloride to improve its strength, and then coats it on the surface of the ceramic gel structure to encapsulate the phase change material in the porous ceramic, thereby preventing the phase change material from leaking or performance degradation to a certain extent. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] A method for preparing a ceramic gel phase change energy storage self-insulating structure in this embodiment includes the following steps:
[0039] Step 1, using iron tailings, silicon nitride and boron nitride as raw materials to prepare a ceramic base material, and then using the ceramic base material, deionized water, a dispersant, a gel monomer, a cross-linking agent, a foaming agent, a foam stabilizer, a catalyst and an initiator as raw materials to prepare a ceramic base green body, and obtaining a porous ceramic after sintering treatment;
[0040] Wherein, the preparation method of ceramic base material is:
[0041] The iron tailings are placed in an oven at 60°C and dried for 48 hours, crushed in a crusher and then dried in an oven at 60°C for 24 hours, then crushed in a crusher again and sieved through a 200-mesh sieve, and the crushed and sieved powder is mixed with silicon nitride and boron nitride in a weight ratio of 4:2:1 to obtain a ceramic base material.
[0042] The dispersant is polyvinyl alcohol, the gel monomer is acrylamide, the cross-linking agent is methylenebisacrylamide, the foaming agent is sodium dodecyl sulfate, the foam stabilizer is dodecanol, the catalyst is tetramethylethylenediamine, and the initiator is ammonium persulfate.
[0043] The preparation method of the ceramic-based green body is as follows:
[0044] S4.1, weigh 100 parts by weight of deionized water, 45 parts by weight of ceramic base material and 1 part by weight of dispersant, pour them into a ball mill and ball mill for 15 hours, after the ball milling is completed, add 85 parts by weight of gel monomer and 9 parts by weight of cross-linking agent and continue ball milling for 2 hours, the obtained result is recorded as the ball milling component;
[0045] S4.2. Add 4 parts by weight of foaming agent and 1 part by weight of foam stabilizer to the ball-milled components, stir at a speed of 1500 r / min for 10 minutes, then add 3 parts by weight of catalyst and 6 parts by weight of initiator, stir at the original speed for 30 seconds, pour into the mold, and after molding and demolding, place in an oven at 45°C and dry for 8 hours to obtain a ceramic-based green body.
[0046] The specific operation method of sintering treatment is:
[0047] The ceramic-based green body is placed in a muffle furnace, first heated to 400°C at a heating rate of 1.5°C / min and kept warm for 30 minutes, then heated to 800°C at a heating rate of 2°C / min and kept warm for 2 hours, and finally heated to 1100°C at a heating rate of 1.5°C / min and kept warm for 4 hours. The porous ceramic is obtained after the furnace is cooled.
[0048] Step 2, pouring ethyl orthosilicate and zirconium oxychloride into ethanol aqueous solution respectively to prepare silica sol and zirconium dioxide sol, and then mixing the silica sol and zirconium dioxide sol to prepare a composite sol;
[0049] Wherein, the preparation method of composite sol is:
[0050] S6.1. Weigh a calculated amount of tetraethyl orthosilicate and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 4. The result is recorded as silica sol. The molar ratio of tetraethyl orthosilicate to ethanol in the silica sol is 1:40.
[0051] S6.2. Weigh a calculated amount of zirconium dioxide oxychloride and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 5. The result is recorded as zirconium dioxide sol. The molar ratio of zirconium dioxide oxychloride to ethanol in the zirconium dioxide sol is 1:40.
[0052] S6.3. Pour the zirconium dioxide sol into the silicon dioxide sol and stir at a speed of 200 r / min for 10 min to obtain a composite sol. The molar ratio of ethyl orthosilicate to zirconium oxychloride in the composite sol is 1:1.
[0053] Step 3, adding propylene oxide and paraffin to the composite sol to prepare an impregnation component, stirring at a speed of 200 r / min for 30 minutes under heating conditions, and then immersing in the preheated porous ceramic, after immersion for 10 minutes, taking out and placing at room temperature for 1 hour, and the obtained structure is recorded as a ceramic gel structure;
[0054] Among them, the weight ratio of the composite sol, propylene oxide and paraffin is 2:1:3, the heating temperature of the heating condition is 95°C, the temperature of the porous ceramic after preheating is 85°C, and the temperature of the impregnated component during the impregnation process is 90°C.
[0055] Step 4: coating a packaging coating on the surface of the ceramic gel structure, and placing it at room temperature for 2 hours to obtain a ceramic gel phase change energy storage self-insulating structure;
[0056] Among them, the specific operation of applying the encapsulation coating is:
[0057] S8.1, weigh 8 parts of carbon fiber, 5 parts of steel fiber, 3 parts of silane coupling agent KH-570 and 100 parts of deionized water, mix them, stir them at 48°C and 300 r / min for 10 min, and freeze-dry them to obtain the reinforcing fiber component;
[0058] S8.2. Weigh 5 parts of reinforcing fiber components and 45 parts of polyvinyl chloride by weight for melt blending, and then coat the melt blended components on the surface of the ceramic gel structure.
[0059] A ceramic gel phase change energy storage self-insulation structure is prepared by a method for preparing a ceramic gel phase change energy storage self-insulation structure.
[0060] Example 2
[0061] A method for preparing a ceramic gel phase change energy storage self-insulating structure in this embodiment includes the following steps:
[0062] Step 1, using iron tailings, silicon nitride and boron nitride as raw materials to prepare a ceramic base material, and then using the ceramic base material, deionized water, a dispersant, a gel monomer, a cross-linking agent, a foaming agent, a foam stabilizer, a catalyst and an initiator as raw materials to prepare a ceramic base green body, and obtaining a porous ceramic after sintering treatment;
[0063] Wherein, the preparation method of ceramic base material is:
[0064] The iron tailings are placed in an oven at 60°C and dried for 48 hours, crushed in a crusher and then dried in an oven at 60°C for 24 hours, then crushed in a crusher again and sieved through a 200-mesh sieve, and the crushed and sieved powder is mixed with silicon nitride and boron nitride in a weight ratio of 4:2:1 to obtain a ceramic base material.
[0065] The dispersant is polyvinyl alcohol, the gel monomer is acrylamide, the cross-linking agent is methylenebisacrylamide, the foaming agent is sodium dodecyl sulfate, the foam stabilizer is dodecanol, the catalyst is tetramethylethylenediamine, and the initiator is ammonium persulfate.
[0066] The preparation method of the ceramic-based green body is as follows:
[0067] S4.1, weigh 100 parts by weight of deionized water, 48 parts by weight of ceramic base material and 2 parts by weight of dispersant, pour them into a ball mill and ball mill for 15 hours, after the ball milling is completed, add 90 parts by weight of gel monomer and 10 parts by weight of cross-linking agent and continue ball milling for 2 hours, the obtained result is recorded as the ball milling component;
[0068] S4.2. Add 5 parts by weight of foaming agent and 2 parts by weight of foam stabilizer to the ball-milled components, stir at a speed of 1500 r / min for 10 minutes, then add 4 parts by weight of catalyst and 7 parts by weight of initiator, stir at the original speed for 30 seconds, pour into the mold, and after molding and demolding, place in an oven at 45°C and dry for 10 hours to obtain a ceramic-based green body.
[0069] The specific operation method of sintering treatment is:
[0070] The ceramic-based green body is placed in a muffle furnace, first heated to 500°C at a heating rate of 1.5°C / min and kept warm for 30 minutes, then heated to 950°C at a heating rate of 2°C / min and kept warm for 2 hours, and finally heated to 1100°C at a heating rate of 1.5°C / min and kept warm for 4 hours. The porous ceramic is obtained after the furnace is cooled.
[0071] Step 2, pouring ethyl orthosilicate and zirconium oxychloride into ethanol aqueous solution respectively to prepare silica sol and zirconium dioxide sol, and then mixing the silica sol and zirconium dioxide sol to prepare a composite sol;
[0072] Wherein, the preparation method of composite sol is:
[0073] S6.1. Weigh a calculated amount of tetraethyl orthosilicate and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 4. The result is recorded as silica sol. The molar ratio of tetraethyl orthosilicate to ethanol in the silica sol is 1:40.
[0074] S6.2. Weigh a calculated amount of zirconium dioxide oxychloride and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 5. The result is recorded as zirconium dioxide sol. The molar ratio of zirconium dioxide oxychloride to ethanol in the zirconium dioxide sol is 1:40.
[0075] S6.3. Pour the zirconium dioxide sol into the silicon dioxide sol and stir at a speed of 200 r / min for 10 min to obtain a composite sol. The molar ratio of ethyl orthosilicate to zirconium oxychloride in the composite sol is 1:1.
[0076] Step 3, adding propylene oxide and paraffin to the composite sol to prepare an impregnation component, stirring at a speed of 200 r / min for 30 minutes under heating conditions, and then immersing in the preheated porous ceramic, after immersion for 10 minutes, taking out and placing at room temperature for 2 hours, and the obtained structure is recorded as a ceramic gel structure;
[0077] Among them, the weight ratio of the composite sol, propylene oxide and paraffin is 2:1:3, the heating temperature of the heating condition is 95°C, the temperature of the porous ceramic after preheating is 90°C, and the temperature of the impregnated component during the impregnation process is 95°C.
[0078] Step 4: Coating a packaging coating on the surface of the ceramic gel structure, and placing it at room temperature for 3 hours to obtain a ceramic gel phase change energy storage self-insulating structure;
[0079] Among them, the specific operation of applying the encapsulation coating is:
[0080] S8.1, weigh 12 parts of carbon fiber, 8 parts of steel fiber, 4 parts of silane coupling agent KH-570 and 100 parts of deionized water, mix them, stir them at 48°C and 300 r / min for 10 min, and freeze-dry them to obtain the reinforcing fiber component;
[0081] S8.2. Weigh 8 parts of reinforcing fiber components and 50 parts of polyvinyl chloride by weight for melt blending, and then coat the melt blended components on the surface of the ceramic gel structure.
[0082] A ceramic gel phase change energy storage self-insulation structure is prepared by a method for preparing a ceramic gel phase change energy storage self-insulation structure.
[0083] Example 3
[0084] A method for preparing a ceramic gel phase change energy storage self-insulating structure in this embodiment includes the following steps:
[0085] Step 1, using iron tailings, silicon nitride and boron nitride as raw materials to prepare a ceramic base material, and then using the ceramic base material, deionized water, a dispersant, a gel monomer, a cross-linking agent, a foaming agent, a foam stabilizer, a catalyst and an initiator as raw materials to prepare a ceramic base green body, and obtaining a porous ceramic after sintering treatment;
[0086] Wherein, the preparation method of ceramic base material is:
[0087] The iron tailings are placed in an oven at 60°C and dried for 48 hours, crushed in a crusher and then dried in an oven at 60°C for 24 hours, then crushed in a crusher again and sieved through a 200-mesh sieve, and the crushed and sieved powder is mixed with silicon nitride and boron nitride in a weight ratio of 4:2:1 to obtain a ceramic base material.
[0088] The dispersant is polyvinyl alcohol, the gel monomer is acrylamide, the cross-linking agent is methylenebisacrylamide, the foaming agent is sodium dodecyl sulfate, the foam stabilizer is dodecanol, the catalyst is tetramethylethylenediamine, and the initiator is ammonium persulfate.
[0089] The preparation method of the ceramic-based green body is as follows:
[0090] S4.1, weigh 100 parts by weight of deionized water, 47 parts by weight of ceramic base material and 2 parts by weight of dispersant, pour them into a ball mill and ball mill for 15 hours, after the ball milling is completed, add 88 parts by weight of gel monomer and 10 parts by weight of cross-linking agent and continue ball milling for 2 hours, the obtained result is recorded as the ball milling component;
[0091] S4.2. Add 4 parts by weight of foaming agent and 2 parts by weight of foam stabilizer to the ball-milled components, stir at a speed of 1500 r / min for 10 minutes, then add 4 parts by weight of catalyst and 6 parts by weight of initiator, stir at the original speed for 30 seconds, pour into the mold, and after molding and demolding, place in an oven at 45°C and dry for 9 hours to obtain a ceramic-based green body.
[0092] The specific operation method of sintering treatment is:
[0093] The ceramic-based green body is placed in a muffle furnace, first heated to 450°C at a heating rate of 1.5°C / min and kept warm for 30 minutes, then heated to 880°C at a heating rate of 2°C / min and kept warm for 2 hours, and finally heated to 1100°C at a heating rate of 1.5°C / min and kept warm for 4 hours. The result after the furnace is cooled is a porous ceramic.
[0094] Step 2, pouring ethyl orthosilicate and zirconium oxychloride into ethanol aqueous solution respectively to prepare silica sol and zirconium dioxide sol, and then mixing the silica sol and zirconium dioxide sol to prepare a composite sol;
[0095] Wherein, the preparation method of composite sol is:
[0096] S6.1. Weigh a calculated amount of tetraethyl orthosilicate and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 4. The result is recorded as silica sol. The molar ratio of tetraethyl orthosilicate to ethanol in the silica sol is 1:40.
[0097] S6.2. Weigh a calculated amount of zirconium dioxide oxychloride and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 5. The result is recorded as zirconium dioxide sol. The molar ratio of zirconium dioxide oxychloride to ethanol in the zirconium dioxide sol is 1:40.
[0098] S6.3. Pour the zirconium dioxide sol into the silicon dioxide sol and stir at a speed of 200 r / min for 10 min to obtain a composite sol. The molar ratio of ethyl orthosilicate to zirconium oxychloride in the composite sol is 1:1.
[0099] Step 3, adding propylene oxide and paraffin to the composite sol to prepare an impregnation component, stirring at a speed of 200 r / min for 30 minutes under heating conditions, and then immersing in the preheated porous ceramic, after immersion for 10 minutes, taking out and placing at room temperature for 2 hours, and the obtained structure is recorded as a ceramic gel structure;
[0100] Among them, the weight ratio of the composite sol, propylene oxide and paraffin is 2:1:3, the heating temperature of the heating condition is 95°C, the temperature of the porous ceramic after preheating is 88°C, and the temperature of the impregnated component during the impregnation process is 93°C.
[0101] Step 4: Coating a packaging coating on the surface of the ceramic gel structure, and placing it at room temperature for 3 hours to obtain a ceramic gel phase change energy storage self-insulating structure;
[0102] Among them, the specific operation of applying the encapsulation coating is:
[0103] S8.1, weigh 10 parts of carbon fiber, 7 parts of steel fiber, 4 parts of silane coupling agent KH-570 and 100 parts of deionized water, mix them, stir them at 48°C and 300 r / min for 10 min, and freeze-dry them to obtain the reinforcing fiber component;
[0104] S8.2. Weigh 7 parts of reinforcing fiber components and 48 parts of polyvinyl chloride by weight for melt blending, and then coat the melt blended components on the surface of the ceramic gel structure.
[0105] A ceramic gel phase change energy storage self-insulation structure is prepared by a method for preparing a ceramic gel phase change energy storage self-insulation structure.
[0106] Comparative Example 1
[0107] The ceramic gel phase change energy storage self-insulating structure and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 1, the boron nitride and silicon nitride in Example 1 are replaced with iron tailings.
[0108] Comparative Example 2
[0109] The ceramic gel phase change energy storage self-insulating structure and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 2, the boron nitride in Example 1 is replaced with silicon nitride.
[0110] Comparative Example 3
[0111] The ceramic gel phase change energy storage self-insulating structure and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 3, the weight ratio of the crushed and screened iron tailings powder to silicon nitride and boron nitride in Example 1 is replaced with 1:3:3.
[0112] Comparative Example 4
[0113] The ceramic gel phase change energy storage self-insulating structure and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 4, the specific operation method of the sintering treatment in Example 1 of heating to 1100°C and keeping warm for 4 hours is replaced by heating to 1000°C and keeping warm for 4 hours.
[0114] Comparative Example 5
[0115] The ceramic gel phase change energy storage self-insulating structure and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 5, the impregnating component in Example 1 is replaced with paraffin.
[0116] Comparative Example 6
[0117] The ceramic gel phase change energy storage self-insulating structure and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 6, the reinforcing fiber component in Example 1 is replaced with carbon fiber.
[0118] Performance Testing
[0119] The specific testing methods and test items are as follows:
[0120] 1. The porous ceramics prepared in Examples 1-3 are recorded as Examples 1, 2 and 3, and the porous ceramics prepared in Comparative Examples 1-4 are recorded as Comparative Examples 1, 2, 3 and 4. According to the standard of GB / T1964-1996 "Test Method for Compression Strength of Porous Ceramics", the compressive strength of the porous ceramics in Examples 1-3 and Comparative Examples 1-4 is tested, and the obtained data are recorded in the following table;
[0121] 2. The porous ceramics prepared in Examples 1-3 are recorded as Examples 1, 2 and 3, and the porous ceramics prepared in Comparative Examples 1-4 are recorded as Comparative Examples 1, 2, 3 and 4. According to the standard of GB / T6569-1986 "Test Method for Bending Strength of Engineering Ceramics", the flexural strength of the porous ceramics in Examples 1-3 and Comparative Examples 1-4 is tested, and the obtained data are recorded in the following table;
[0122] 3. The ceramic gel phase change energy storage self-insulating structures prepared in Examples 1-3 and Comparative Examples 5-6 are marked as Example 1, Example 2, Example 3, Comparative Example 5 and Comparative Example 6, respectively. Then, they are placed in an open crucible and placed in a heating furnace at 100° C. for 20 minutes to ensure that the paraffin is completely melted. The crucible is then taken out and placed in the air to cool for 20 minutes to complete the solidification process. This is recorded as one melting / solidification process. Examples 1-3 and Comparative Examples 5-6 are subjected to 100 melting / solidification processes, and their mass loss rate and thermal conductivity loss rate are tested. The specific formula is:
[0123] Mass loss rate = (m 0 -m 1 ) / m 0
[0124] Thermal conductivity loss rate = (k 0 -k 1 ) / k 0
[0125] Among them, m 0 is the initial mass of the ceramic gel phase change energy storage self-insulation structure, m 1 It is the mass of the ceramic gel phase change energy storage self-insulation structure after 100 melting / solidification processes;
[0126] k 0 is the initial thermal conductivity of the ceramic gel phase change energy storage self-insulation structure, k 1 It is the thermal conductivity of the ceramic gel phase change energy storage self-insulation structure after 100 melting / solidification processes;
[0127] The obtained data are recorded in the following table;
[0128]
[0129]
[0130] It can be seen from the data in the above table that the porous ceramics prepared in Examples 1-3 have higher compressive strength and flexural strength than those in Comparative Examples 1-2, indicating that the porous ceramics prepared with iron tailings, silicon nitride and boron nitride as raw materials have better mechanical properties than the porous ceramics prepared with only iron tailings and the porous ceramics prepared with iron tailings and silicon nitride as raw materials, indicating that iron tailings, silicon nitride and boron nitride can play a synergistic role.
[0131] Secondly, the present invention changes the weight ratio of iron tailings, silicon nitride and boron nitride, thereby reducing the iron tailings content in the raw materials for preparing porous ceramics. The compressive strength and flexural strength of the porous ceramics prepared in Comparative Example 3 are smaller than those in Examples 1-3, but the cost is increased to a certain extent, because the cost of iron tailings is lower than that of silicon nitride and boron nitride. Therefore, it is shown that the ratio of the amounts of iron tailings, silicon nitride and boron nitride in the present invention can maximize the reduction of production costs while maintaining the performance of porous ceramics; the porous ceramics prepared in Comparative Example 4 by lowering the sintering temperature have lower compressive strength and flexural strength than those in Examples 1-3, because the sintering temperature in Comparative Example 4 is not enough, which will lead to incomplete sintering to a certain extent, so that the sintered porous ceramics contain more reactants or impurities, and sintering the porous ceramics at the temperature in Examples 1-3 can prevent incomplete sintering, thereby improving the mechanical properties of the porous ceramics.
[0132] Secondly, the ceramic gel phase change energy storage self-insulating structure prepared in the present embodiments 1-3 has lower mass loss rate and thermal conductivity loss rate than that of comparative examples 5-6, indicating that the phase change material prepared by mixing silica sol and zirconium dioxide sol and adding paraffin has better thermal stability than single paraffin, and the addition of carbon fiber and steel fiber modified by silane coupling agent KH-570 to polyvinyl chloride can also improve the thermal stability of the ceramic gel phase change energy storage self-insulating structure.
[0133] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0134] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a ceramic gel phase change energy storage self-insulation structure, characterized in that: The preparation method comprises the following steps: Step 1, using iron tailings, silicon nitride and boron nitride as raw materials to prepare a ceramic base material, and then using the ceramic base material, deionized water, a dispersant, a gel monomer, a cross-linking agent, a foaming agent, a foam stabilizer, a catalyst and an initiator as raw materials to prepare a ceramic base green body, and obtaining a porous ceramic after sintering treatment; Step 2, pouring ethyl orthosilicate and zirconium oxychloride into ethanol aqueous solution respectively to prepare silica sol and zirconium dioxide sol, and then mixing the silica sol and zirconium dioxide sol to prepare a composite sol; Step 3, adding propylene oxide and paraffin to the composite sol to prepare an impregnation component, stirring at a speed of 200 r / min for 30 minutes under heating conditions, and then immersing in the preheated porous ceramic, after immersion for 10 minutes, taking out and placing at room temperature for 1-2 hours, and the obtained structure is recorded as a ceramic gel structure; Step 4: Coat a packaging coating on the surface of the ceramic gel structure, and obtain a ceramic gel phase change energy storage self-insulating structure after drying.
2. The method for preparing a ceramic gel phase change energy storage self-insulation structure according to claim 1, characterized in that: In step 1, the ceramic base material is prepared by: The iron tailings are placed in an oven at 60°C and dried for 48 hours, crushed in a crusher and then dried in an oven at 60°C for 24 hours, then crushed in a crusher again and sieved through a 200-mesh sieve, and the crushed and sieved powder is mixed with silicon nitride and boron nitride in a weight ratio of 4:2:1 to obtain a ceramic base material.
3. The method for preparing a ceramic gel phase change energy storage self-insulation structure according to claim 1, characterized in that: In step 1, the dispersant is polyvinyl alcohol, the gel monomer is acrylamide, the cross-linking agent is methylenebisacrylamide, the foaming agent is sodium dodecyl sulfate, the foam stabilizer is dodecyl alcohol, the catalyst is tetramethylethylenediamine, and the initiator is ammonium persulfate.
4. The method for preparing a ceramic gel phase change energy storage self-insulation structure according to claim 1, characterized in that: In step 1, the ceramic-based green body is prepared by: S4.1, weigh 100 weight parts of deionized water, 45-48 weight parts of ceramic base material and 1-2 weight parts of dispersant, pour them into a ball mill and ball mill for 15 hours, after the ball milling is completed, add 85-90 weight parts of gel monomer and 9-10 weight parts of cross-linking agent and continue ball milling for 2 hours, the obtained result is recorded as the ball milling component; S4.
2. Add 4-5 parts by weight of foaming agent and 1-2 parts by weight of foam stabilizer to the ball-milled components, stir at a speed of 1500r / min for 10 minutes, then add 3-4 parts by weight of catalyst and 6-7 parts by weight of initiator, stir at the original speed for 30 seconds, pour into the mold, and after molding and demolding, place in an oven at 45°C and dry for 8-10 hours to obtain a ceramic-based green body.
5. The method for preparing a ceramic gel phase change energy storage self-insulation structure according to claim 1, characterized in that: In step 1, the specific operation method of the sintering process is: The ceramic-based green body is placed in a muffle furnace, first heated to 400-500°C at a heating rate of 1.5°C / min and kept warm for 30 minutes, then heated to 800-950°C at a heating rate of 2°C / min and kept warm for 2 hours, and finally heated to 1100°C at a heating rate of 1.5°C / min and kept warm for 4 hours. The porous ceramic is obtained after the furnace is cooled.
6. The method for preparing a ceramic gel phase change energy storage self-insulation structure according to claim 1, characterized in that: In step 2, the preparation method of the composite sol is: S6.
1. Weigh a calculated amount of tetraethyl orthosilicate and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 4. The result is recorded as silica sol. The molar ratio of tetraethyl orthosilicate to ethanol in the silica sol is 1:
40. S6.
2. Weigh a calculated amount of zirconium dioxide oxychloride and pour it into an ethanol aqueous solution with a volume fraction of 80%. Add nitric acid dropwise under stirring at a speed of 200 r / min to adjust the pH value to 5. The result is recorded as zirconium dioxide sol. The molar ratio of zirconium dioxide oxychloride to ethanol in the zirconium dioxide sol is 1:
40. S6.
3. Pour the zirconium dioxide sol into the silicon dioxide sol and stir at a speed of 200 r / min for 10 min to obtain a composite sol. The molar ratio of ethyl orthosilicate to zirconium oxychloride in the composite sol is 1:
1.
7. The method for preparing a ceramic gel phase change energy storage self-insulation structure according to claim 1, characterized in that: In step 3, the weight ratio of the composite sol, propylene oxide and paraffin is 2:1:3, the heating temperature of the heating condition is 95°C, the temperature of the preheated porous ceramic is 85-90°C, and the temperature of the impregnated component during the impregnation process is 90-95°C.
8. The method for preparing a ceramic gel phase change energy storage self-insulation structure according to claim 1, characterized in that: In step 4, the specific operation of applying the encapsulation coating is as follows: S8.1, weigh 8-12 parts of carbon fiber, 5-8 parts of steel fiber, 3-4 parts of silane coupling agent KH-570 and 100 parts of deionized water, mix them, stir them at 48°C and 300 r / min for 10 min, and freeze-dry them to obtain the reinforcing fiber component; S8.
2. Weigh 5-8 parts of reinforcing fiber components and 45-50 parts of polyvinyl chloride by weight for melt blending, and then coat the melt blended components on the surface of the ceramic gel structure.
9. The method for preparing a ceramic gel phase change energy storage self-insulation structure according to claim 1, characterized in that: In step 4, the specific operation of the drying treatment is to place it at room temperature for 2-3 hours.
10. A ceramic gel phase change energy storage self-insulation structure, characterized in that: The ceramic gel phase change energy storage self-insulating structure is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Cited By
Silicon nitride ceramic-based composite material and preparation method thereof
CN121063944A
